Implementasi UML Dan Grennfoot Untuk Membangun Aplikasi Pengucapan Bahasa Inggris - Wire Bagye; M. Taufan Asri Zaen (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
One of the materials in the English Language course is listening, namely the skill of hearing the pronunciation of English sentences. Learning listening must use native speaker or recording material so that the pronunciation is heard according to the original. If you use the course participants as a sound source, there is a high probability of mistakes in the pronunciation of words or sentences. Then an application is needed to help with course activities as tutors or native speakers in giving correct English pronunciation. In this research, English Pronunciation Application was built using the Greenfoot Application with the object oriented programming concept. This application is to help pronoun learning that can output audio when the object clicked. The development method uses SDLC, application modeling uses UML and testing using Black-box testing. The English pronunciation application is compiled into a .jar file so that it can be run on a computer with a Windows operating system that has JDK installed. The test results show that this English learning application can replace tutors, produce the right audio, and can replace native speakers. This can be seen from the results of the questionnaire showing 82%.